Do Malaysian asthma patients use asthma action plan? a cross sectional study in Malaysian primary care setting - Salim, Hani Syahida; Lee, Ping Yein; Shariff Ghazali, Sazlina; Cheong, Ai Theng; Pinnock, Hilary; Harrun, Noor Harzana; Mohamed Isa, Salbiah; Aris, Junita; Seetharaman, Vengketeswara Rao; Nordin, Salmah; Mahmud, Maimunah; Lee, Yeow Siong (European Respiratory Society, 2018)
Background: Supported self-management, including provision of an asthma action plan (AAP) improves asthma control. However, the concept of self-management and use of AAP among Asian population is relatively new. Aims: To determine the prevalence of AAP ownership among asthma patients and their characteristics in Malaysia primary care. Methods: We randomly sampled 550 asthma patients from five primary care practices between Oct 2017-Jan 2018. The patients were interviewed with pre-tested questionnaires to assess their AAP ownership, socio-demographic and the Asthma Control Test (ACT). Descriptive statistics were used to analyse the data. Results: Asthma control was poor in 143(26%) patients, partially controlled in 137(24.9%) and well-controlled in 270(29.1%). Only 160(29.1%) owned an AAP. These AAP were primarily given by the doctors (95%, n=152) and 5% were given by the allied health (nurses and pharmacists). Among those who owned an AAP, 106(66.2%) were confident to use it. For those using AAP, the mean age was 45.6 years old, predominantly female (67%), of Malay ethnicity (48%), had at least secondary educational level (40%) and had well-controlled asthma (46%). Conclusion: Education, usage and confidence in using an AAP for asthma self-management is sub-optimal among asthma patients in Malaysian primary care. Supported asthma self-management in this population must be strengthened.